Transforming Medusa - Currie, Charlotte (Amaltea. Revista de Mitocrítica, 2011)
The mythic figure of Medusa is inherently linked with the idea of transformation; both her transformation from beautiful woman to monster as well as her ability to transform all who meet her gaze into statues have become fundamental elements of her story. While both these aspects of her character appear to be late additions to her myth, the idea of Medusa as a figure who both transforms and is transformed nevertheless became canonical and indeed she continues to transform throughout her subsequent history of reception. This paper will seek to understand the early mythic life of Medusa as a transformation before examining the disparate transformations she then endures, from the ancient period to the present day.